Community Participation in Organization Election of Local Head at the Time of the Covid-19 Pandemic in 2020 in Banten Province (Case Study: Serang Regency, Pandeglang Regency, Cilegon City and South Tangerang City) - Dairul Dairul; Bahrullah Akbar; Aries Djaenuri; Sampara Lukman (Budapest International Research and Critics University, 2022)
In community participation, the implementation of regional head elections is the embodiment of the representative function inherent in the sovereignty of the people. The function of representation is one of the functions of government. For this reason, the selection represents the object of the form of Government Science. This study is to measure